The limitations of the International Drug Conventions - Chatterjee, S.K. (Drug policies in Western Europe, 1989)
Drug-based issues and problems are multi-dimensional; their effective resolution therefore requires multi-disciplinary action at national, regional and international levels. International Drug Conventions· have their limits; they can recommend measures and the international institutions concerned offer their co-operation in the promotion of an international cause.